SEMANTIC STUDY OF METAPHORS IN POETRY: LINGUISTIC AND LITERARY APPROACHES - Anita Febiana Putri; Wulan Astriani; Aidil Syah Putra (Media Inovasi Pendidikan dan Publikasi, 2024)
This study examines the use of metaphors in poetry through both linguistic and literary lenses. By analyzing cognitive structures and conceptual mappings, we explore how metaphors transform abstract ideas into tangible imagery, enhancing thematic depth and emotional resonance. The integration of cognitive linguistics and literary criticism reveals the dual function of metaphors: as cognitive tools shaping understanding and as artistic devices enriching poetic expression. Through detailed case studies, we demonstrate the interdisciplinary nature of metaphor analysis, offering insights into the cognitive and aesthetic dimensions of metaphorical language. This research underscores the importance of metaphors in both linguistic and literary contexts, contributing to a comprehensive understanding of their role in poetry